REPRESENTASI SIMBOL CANDI HINDU DALAM KEHIDUPAN MANUSIA: KAJIAN LINGUISTIK ANTROPOLOGIS - Arifin, Ferdi (Universitas Muhammadiyah Surakarta, 2015)
Tempel is well-know as herritage building which has high value on history and it is protected by Indonesian government. It represents not only as a herritage building but also history of human life. Temple always shows many symbols that give messages to society. This research examines temple as a representation of human life using qualitative method on language and culture. The data are collected both through direct observation and interview with scholars on archaeology. The findings show language used on the temple?s epigraph represent human life of the ancient society. The epigraph presents human life story which gives messages for future society about a good way of life.